Enhancing Naturalness of Pen-and-Tablet Drawing through Context Sensing - Sun, Minghui; Cao, Xiang; Song, Hyunyoung; Izadi, Shahram; Benko, Hrvoje; Guimbretiere, Francois; Ren, Xiangshi; Hinckley, Ken (ITS '11 Proceedings of the ACM International Conference on Interactive Tabletops and Surfaces Pages 83-86, 2011)
Among artists and designers, the pen-and-tablet combination is widely used for creating digital drawings, as digital pens outperform other input devices in replicating the experience of physical drawing tools. In this paper, we explore how contextual information such as the relationship between the hand, the pen, and the tablet can be leveraged in the digital drawing experience to further enhance its naturalness. By embedding sensors in the pen and the tablet to sense and interpret these contexts, we demonstrate how several physical drawing practices can be reflected and assisted in digital interaction scenarios.